2017
DOI: 10.1007/s13300-017-0279-y
|View full text |Cite
|
Sign up to set email alerts
|

Ipragliflozin Reduces Epicardial Fat Accumulation in Non-Obese Type 2 Diabetic Patients with Visceral Obesity: A Pilot Study

Abstract: IntroductionEpicardial fat (EF) was reported to be independently associated with cardiovascular disease regardless of obesity. We have previously reported that a sodium-glucose co-transporter-2 (SGLT2) inhibitor, luseogliflozin, reduces the EF volume (EFV) in parallel with the reduction of body weight in obese patients (BMI ≥25 kg/m2) with type 2 diabetes. However, it is unknown whether SGLT2 inhibitors could reduce EFV in non-obese patients (BMI <25 kg/m2) with type 2 diabetes. Therefore, we evaluated the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 48 publications
3
60
1
3
Order By: Relevance
“…Furthermore, the present results suggest that ipragliflozin reduced the serum leptin concentration and might thereby have increased appetite. SGLT‐2 inhibitors have been found to reduce serum leptin levels, but a reduction in the circulating leptin concentration adjusted for bodyweight has not previously been reported. The present study thus suggests that ipragliflozin might have reduced the circulating leptin concentration by an unknown mechanism.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the present results suggest that ipragliflozin reduced the serum leptin concentration and might thereby have increased appetite. SGLT‐2 inhibitors have been found to reduce serum leptin levels, but a reduction in the circulating leptin concentration adjusted for bodyweight has not previously been reported. The present study thus suggests that ipragliflozin might have reduced the circulating leptin concentration by an unknown mechanism.…”
Section: Discussionmentioning
confidence: 95%
“…Treatment with SGLT2 inhibitors is poised to ameliorate many of the pathophysiological abnormalities seen in HFpEF. 14 In clinical trials, the use of SGLT2 inhibitors has been shown to reduce the quantity of epicardial adipose tissue (independently of effect on body weight), [35][36][37] and these drugs ameliorate the inflammation of adipose tissue surrounding the heart and great vessels 38,39 and the associated abnormalities of cardiac filling and aortic distensibility in both experimental and clinical HFpEF. 18,[40][41][42] Furthermore, SGLT2 inhibitors act to inhibit sodium reabsorption in the proximal renal tubules, in which the majority of renal sodium retention occurs [43][44][45] ; this action explains the marked reduction in plasma and/or interstitial volume and haemoconcentration seen in randomized controlled trials in type 2 diabetes.…”
Section: Sample Size Calculations and Study Conductmentioning
confidence: 99%
“…In epidemiological surveys, epicardial fat volume (EFV) is shown to be positively correlated with the risk of atherosclerosis and coronary events . In Japanese patients with T2DM with or without obesity, ipragliflozin and luseogliflozin reduced EFV (measured by magnetic resonance imaging) at 12 weeks (change from baseline: luseogliflozin, 6 cm 3 , P = 0.048; ipragliflozin, 13 cm 3 ; P = 0.008), which correlated with reduction in circulating CRP levels …”
Section: Role Of Sglt‐2 Inhibitors In Patients With T2dm and Multiplementioning
confidence: 99%